An unusual cause for a dilated right heart 33-years post-surgical repair of aortic coarctation - Kyriakakis, Charles G.; Van Rensburg, Annari; Ntusi, Ntobeko; Janson, Jacques T.; Herbst, Philip G.; Doubell, Anton F. (SA Heart Journal, 2018)
Prior to planning for the surgical correction of a congenital cardiac defect it is of the utmost importance that additional defects, which themselves might also require surgical correction, be sought and identified. Of these, those leading to volume overload of the right heart, and particularly those that are not easily identified on transthoracic echocardiography, may go unnoticed during initial evaluation in childhood. We describe the approach to such a clinical problem, highlighting the value of multimodality imaging in this context, and outline the options available for surgical correction.